Saltmarsh reclamation enhances plant species richness and reduces soil macrofaunal biomass by regulating soil properties through elevation - Zhang, Guangzhi; Wang, Shanshan; Xu, Mingshan; Hu, Hao; Huang, Junbao; Gan, Jianjun; Chen, Zhentao; Zeng, Jian (Frontiers in Ecology and Evolution, 2025)
Globally, saltmarsh reclamation results in significant losses of coastal wetlands. However, the impacts on above- and below-ground biodiversity and the underlying mechanisms remain poorly understood. We hypothesized that saltmarsh reclamation differently affects plant and soil macrofaunal communities by regulating soil properties through elevation. To test this, we surveyed 36 plots in Sheyang County, eastern China and used t-tests, redundancy analysis, and structural equation modeling to examine differences and the direct/indirect effects of elevation and soil physico-chemical properties on plant and soil macrofaunal diversity. Results showed that plant species richness in reclaimed areas was significantly higher than that in saltmarshes, whereas the total and average biomass of soil macrofauna exhibited an inverse pattern. Plant species richness positively associated with elevation but negatively correlated with soil available phosphorus (AP) and electrical conductivity (EC). The total and average biomass of soil macrofauna positively correlated with soil ammonium nitrogen (AN), total nitrogen (TN), total potassium (TK), and inversely related to total phosphorus (TP), elevation, mud content (SMC). Elevation indirectly increased plant species richness via soil water content (SWC), total carbon (TC), AN, and nitrate nitrogen (NN), but decreased it through bulk density (BD). For soil macrofauna, elevation indirectly reduced total biomass via SWC, TC, and AN, while indirectly increasing it through available potassium (AK). These findings elucidate the mechanisms driving above- and below-ground biodiversity changes following saltmarsh reclamation, providing a comprehensive understanding of these ecological alterations.